(untitled) (Research, Society and Development, 2020)
This review aims to show evidence of possible neuroprotective agents, and to identify new avenues for possible intervention, in search of neuroprotection in patients affected by depression. It is a narrative review that used PubMed, Lilacs, Scielo, Cochrane and Latindex as a database, in the period between 2015 to 2020, resulting in 1009 articles and 19 different articles using selection criteria. Neuropsychiatric disorders, including depression, often exhibit a neuroprogressive course from the prodrome to chronicity. There are a variety of agents exhibiting the ability to attenuate biological mechanisms associated with neuroprogression. Signs of evidence of clinical neuroprotection are evident when evaluating studies by different authors. The adjuvant use of multiple drug agents may present a viable path for the clinical realization of neuroprotection. Definitive prospective studies on neuroprotection with multimodal assessment are needed.